(3jGbhJ GdcdGe ajeG fGH GdTGes - (3GHf MLI GdMehj , CHh HcQ Hf Ydj Hf YHO Gddg GdMehj GdGRQGQj, Jbj GdOjf GHf MLg,J (B837 (3g` s ((3eMeO Hf CMeO GdedG GdMdHi s)
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje , cGf Pdc ai GdcJGH eSWhQkG s
(3BNQgG (B:s
(3aCYGP Gddg ehdGfG hHdGOg ef gPg GdbjGeg GdbGFeg s
(3GfXQ CjVkG MQjb OeTb Qbe (B1027s
(3hgj QSGdI ai MQjb OeTb SfI (B791 (3cJHgG GdeDda Edi GdbGVi aNQ GdOjf Hf ecGfS HGdbGgQIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B67 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B67s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B339 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs